Influence of Deposition Condition on Y2O3 Coatings Produced by Pulsed Electrophoretic Deposition - Hidetoshi Miyazaki; Asumi Ichikawa; Hisao Suzuki; Toshitaka Ota (Advances in Materials Science and Engineering)
Y2O3 nanoparticle suspension aqueous solution was prepared using citric acid. Then, Y2O3 film was deposited using this solution with pulsed electrophoretic deposition (EPD). A dense Y2O3 film of 25.7 μm thickness was obtained with deposition conditions of 0.5 wt% Y2O3 concentration, bias voltage of 0.5 V, and bias frequency of 1 kHz. The respective resistivities of the as-deposited film and films heat-treated at 200°C and 400°C were 2.84 × 103 Ω·cm, 5.36 × 104 Ω·cm, and 2.05 × 106 Ω·cm. A 59.8 μm thick dense Y2O3 film was obtained using two-step deposition with change of the bias voltage: a first step of 0.5 V and a second step of 2.0 V.